2023
DOI: 10.1021/acs.bioconjchem.2c00551
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of the Human Epididymis Protein-4 (HE4) Ovarian Cancer Biomarker through a Sandwich-Type Immunoassay Method with Laser-Induced Breakdown Spectroscopy

Abstract: Detection of cancer before the appearance of any symptoms is crucial for successful treatment. Early detection is, however, very challenging, particularly for the types of cancer with few or no symptoms at early stages, such as epithelial ovarian cancer (EOC). Developing a user-friendly method that can detect biomarkers with sufficient selectivity, sensitivity, and reproducibility is a promising approach for overcoming the challenges of early detection of EOC. In this study, we report a sandwich-type micropart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In addition to the above, cancer diagnosis is also a primary focus for quantitative analysis of biomarkers using LIBS and LA-ICP-MS. A sandwich immunoassay for the Human Epididymis protein-4 (HE4) ovarian cancer biomarker was developed using LIBS measurement of bound Si particles. 200 The authors acknowledged limitations in the clinical utility of this assay with regards to lack of specicity due to non-specic crosscoupling and the limited dynamic range (0.0-0.0073 pmol L −1 ) which necessitated serial sample dilution. 200 Veverkova et al reported adaptations to their previously described sandwich immunoassay for metallothionein with LA-ICP-MS readout.…”
Section: Elements As Tags For Indirect Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above, cancer diagnosis is also a primary focus for quantitative analysis of biomarkers using LIBS and LA-ICP-MS. A sandwich immunoassay for the Human Epididymis protein-4 (HE4) ovarian cancer biomarker was developed using LIBS measurement of bound Si particles. 200 The authors acknowledged limitations in the clinical utility of this assay with regards to lack of specicity due to non-specic crosscoupling and the limited dynamic range (0.0-0.0073 pmol L −1 ) which necessitated serial sample dilution. 200 Veverkova et al reported adaptations to their previously described sandwich immunoassay for metallothionein with LA-ICP-MS readout.…”
Section: Elements As Tags For Indirect Determinationsmentioning
confidence: 99%
“…200 The authors acknowledged limitations in the clinical utility of this assay with regards to lack of specificity due to non-specific cross-coupling and the limited dynamic range (0.0–0.0073 pmol L −1 ) which necessitated serial sample dilution. 200 Veverkova et al reported adaptations to their previously described sandwich immunoassay for metallothionein with LA-ICP-MS readout. 183 Magnetic particles were modified by molecularly imprinted polymers and incubated with sample and spotted onto PVDF for LA-ICP-MS analysis.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%
“…11 Bioconjugates have the potential to improve the sensitivity and selectivity of in vitro assays for early detection by conjugating nanomaterials to molecules of interest to increase the sensitivity while preserving specificity. 12 We need to think about assays that can be used in primary care spaces and clinics where people are most likely to be able to access screening. Assays need to be low cost and not require complex equipment to help move screening into more accessible environments to reach underserved populations.…”
Section: ■ Biomarkersmentioning
confidence: 99%